2014
DOI: 10.1021/cs500587b
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Intra- and Intermolecular C–H Arylation Using Mesylates: Synthetic Scope and Mechanistic Studies

Abstract: This paper describes the development of Pd-catalyzed inter- and intramolecular direct arylation using mesylates. Furthermore, a sequential mesylation/arylation protocol using phenols as substrates is described. These transformations are general with respect to the electronics of the C–H substrates and allow for the synthesis of diverse heterocyclic motifs in good yields. Both arenes and heteroarenes efficiently participate in these reactions. Preliminary mechanistic studies are presented for both inter- and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In this case, the excellent yields of desired products were achieved with a variety of aryl bromides in the presence of 0.25% complex 4 without any additive. Moreover, in most reported arylation protocols, excessive base (typically 2–5 equiv) was necessary to obtain good results. In our system, 1.0 equiv of base was enough to complete the arylation with the excellent yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the excellent yields of desired products were achieved with a variety of aryl bromides in the presence of 0.25% complex 4 without any additive. Moreover, in most reported arylation protocols, excessive base (typically 2–5 equiv) was necessary to obtain good results. In our system, 1.0 equiv of base was enough to complete the arylation with the excellent yields.…”
Section: Resultsmentioning
confidence: 99%
“…Punji , utilized an unsymmetrical pincer PCN/Pd complex (0.5% catalyst, Figure ) to catalyze the direct Csp 2 –H arylation of benzoxazole, but CuI was necessary as a cocatalyst in this system and the substrates were limited to only aryl iodides. The versatile applications of 2-substituted benzoxazoles were taken into consideration, but to date, the reported arylation systems of benzoxazoles, whichever Pd and Ni systems or Pd/Cu system, had typical limitations, including the high loading of catalysts, activated substrates, and complicated catalyst systems.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary study revealed that the direct oxidative C-H arylation of arylsulfonyl hydrazides with benzoxazole using a series of indolylphosphines (L1a & L4a-L4c) was possible [51]. Recently, Kalyani and co-workers improved the scope of direct arylation of benzoxazoles with aryl mesylates [52], yet CM-phos (L1a) gave moderate activity during their screening process.…”
Section: Direct C-h Arylationmentioning
confidence: 99%
“…The synthetic approaches to prepare dibenzofurans can be classified into two main categories. One involves the construction of the dibenzofuran from diaryl ethers. The mechanism proposed for the formation of the new C–C bond proceeds through three sequential steps, in the presence of Pd, , Rh or Ag …”
Section: Introductionmentioning
confidence: 99%